Komunikasi Interpersonal pada Pelayanan Customer Service dalam Mempertahankan Reputasi di Gunung Sahari Laboratorium - Irsalina, Rosalia; Hardian, Arvin; Ekowati, Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Service strategy is seen from the efforts made by a company or entity to improve the quality and efficiency of Customer Service. A laboratory must carry out service activities that can make its customers feel satisfied. Service is defined as an action or deed of a person or organization to provide satisfaction to customers or fellow employees. The purpose of this study was to determine Interpersonal Communication in Customer Service in Maintaining Reputation at Gunung Sahari Laboratory. This research is a qualitative study. Data collection was carried out by interview and google review survey. Data analysis using the interactive analysis model. The results of the study on Interpersonal Communication in Customer Service in Maintaining Reputation at Gunung Sahari Laboratory, can be concluded several important things. The implementation of effective interpersonal communication has been shown to have a significant role in maintaining the company's reputation. Aspects of communication, both verbal and non-verbal, which are carried out properly, have been shown to have a major impact on maintaining the positive image of Gunung Sahari Laboratory. Gunung Sahari Laboratory is advised to carry out routine training on interpersonal communication, both verbal and non-verbal, in order to improve the quality of service on an ongoing basis. In addition, periodic evaluation of the implementation of Customer Service communication standards.